2021
DOI: 10.1177/20503121211060614
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of urinary tract infection and determinant factors among diabetic patients at Dessie Referral Hospital, South Wollo, Northeast Ethiopia

Abstract: Introduction: Diabetic patients have a higher tendency of developing all infections, especially infections of the genitourinary tract. Urinary tract infections cause considerable disorders in diabetic patients, and if complicated, can cause renal failure. In Ethiopia, the magnitude of diabetes mellitus-associated urinary tract infections increased from 7.1% in 2005 to 33.9% in 2019. The successful management of patients suffering from urinary tract infections in diabetic patients depends upon the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…A possible explanation for the elevated UTI in diabetes individuals is nerve damage induced by hyperglycemia, which affects the tissue bladder's capacity to perceive the presence of urine, allowing urine to remain in the stream for longer periods of time, which encourages bacteria to proliferate and propagate, raising infection ( 25 ). Other studies have corroborated similar conclusions to our study ( 21 , 22 , 26 ), reporting that UTIs are particularly common in diabetes patients. While kidney disease is one of the risk factors for UTIs, the patient's immune system is weakened, making them more susceptible to UTIs ( 21 , 22 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for the elevated UTI in diabetes individuals is nerve damage induced by hyperglycemia, which affects the tissue bladder's capacity to perceive the presence of urine, allowing urine to remain in the stream for longer periods of time, which encourages bacteria to proliferate and propagate, raising infection ( 25 ). Other studies have corroborated similar conclusions to our study ( 21 , 22 , 26 ), reporting that UTIs are particularly common in diabetes patients. While kidney disease is one of the risk factors for UTIs, the patient's immune system is weakened, making them more susceptible to UTIs ( 21 , 22 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Patients with a history of UTI might be more cautious to seek medical attention when UTI symptoms emerge, which is a possible explanation. The current study further found an increased risk of UTI among patients with diabetes for more than five years, which is in line with a study in Ethiopia [2]. This could be due to the long-term effects of diabetes, such as neuropathy and an impaired immune system.…”
Section: Discussionsupporting
confidence: 92%
“…Globally, it is estimated that about 150 million individuals are affected by urinary tract infections (UTIs) annually, with a significant number of those affected being diabetics [1][2][3]. The 2016 WHO report has shown that there is a marked increase in the number of people affected by diabetes, and this trend is scheduled to grow in geometric proportions in the next couple of decades [4].…”
Section: Introductionmentioning
confidence: 99%
“…We examined numerous study to assess the association of sex with UTI in diabetic patients. Accordingly, female sex was reported to be a factor with UTI by four primary studies included in this review [ 35 , 38 , 41 , 43 ]. A total of 1071 subjects were included to analyze the association of female sex with UTI.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, all the included studies was conducted in institutional bases. Four in Addis Ababa [30][31][32][33], Four in Amhara [34][35][36][37], Three in Southern Nations Nationalists and Peoples Region (SNNP) [38][39][40], two in Oromia [41,42], and one study in Harari [43]. All studies in this review adopted a cross-sectional design.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%